THE DIGITAL CONSERVATION AND REVITALIZATION OF REGIONAL LANGUAGES IN NUSANTARA - Munawwir Hadiwijaya; Kingkin Puput Kinanti; Ike Dian Puspita Sari (UIBU, 2022)
The purpose of this research is the digitization of regional languages of Indonesia. The form of technology that was developed is a digital conservation and revitalization program. The development model that will be used in this program is the modified Borg and Gall development research model. There are six aspects that are assessed, namely aspects of linguistic, aspects of aesthetic appeal, features of media relevance, aspects of content arrangement, aspects of software engineering, aspects of effects on learning techniques. After using the app for roughly a month, students gave it an average rating of 4.72, and professionals gave it a rating of 4.52 using a grade range of 1 to 5.